ANALISIS EFEKTIFITAS PELAKSANAAN PRAKTEK KERJA LAPANGAN (PKL) MAHASISWA AKADEMI REFRAKSI OPTISI YLPTK PADANG - Alvia Wesnita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the effectiveness of street vendors' implementation of YLPTK Padang Optisi Refraction Academy (ARO) Academic Year 2016/2017. This study analyzes the effectiveness of PKL programs with the CIPP model (context, input, process, product). This research is quantitative descriptive, which uses a questionnaire with a Likert scale for data collected from respondents. Sampling was done by total sampling, as many as 50 students. Data were analyzed by descriptive analysis. Based on the findings, it can be concluded that the effectiveness of the PKL program in ARO YLPTK Padang in the 2016/2017 academic year is categorized as effective, judging from the variables, input, process and results.